Risk-Oriented Characteristics of Current Epidemiological Situation on Crimean Hemorrhagic Fever in the Astrakhan Region - A. A. Kovalevskaya; O. L. Vasil’kova; B. L. Agapov; E. V. Kouklev; V. A. Safronov; Yu. I. Yashechkin; V. P. Toporkov; S. A. Shcherbakova; N. N. Nikeshina; L. N. Noskova; T. E. Arshba; G. G. Rudenko; et al. (Проблемы особо опасных инфекций, 2018)
Objective - risk-oriented assessment of current epidemiological situation on Crimean hemorrhagic fever (CHF) in the Astrakhan Region. Materials and methods. Documents and reports of the Astrakhan Plague Control Station, Rospotrebnadzor Administration in the Astrakhan Region, and A.M. Nichogi Regional Infectious Clinical Hospital were utilized for the study. Key method of investigation was epidemiological analysis of morbidity rates among the population of the Astrakhan Region over the period of 2000-2016. The subject of the epidemiological analysis - 125 case histories. Results and conclusions. As a result of retrospective epidemiological analysis basic risk categories as regards Crimean hemorrhagic fever infection in the Astrakhan Region between 2000 and 2016 were identified and characterized. It was established that men of older ages are more prone to the disease (80 out of 125 cases - 64.0 %, 31-50 years old - 32 % and 51-70 years old - 14.4 %). Among the feminine population, CHF cases are also common within the same age range. High risk territories turned out to be 3 districts of the Region (Privolzhsky, Enotaevsky, Krasnoyarsky), medium risk - 3 districts, low risk - 4, and very low - 2. Risk group analysis revealed that during the last decade, CHF infection is more often registered in unemployed persons - 43.2 %, retired people - 17.6 %, and to a lesser degree - in salaried workers (10.4 %), agricultural laborers, and farm workers (8.8 %). In the majority of the cases (83-66.4 %) human infection with CHF occurred through the bite of a tick, or at the attempt to remove or crush it with unprotected hands. In 26 cases (20.8 %), risk factors were not identified. CHF in the Astrakhan Region has a pronounced spring - summer seasonality with the onset in the second half of April, peak values - in June (45 cases - 36 %) and a decline - in August. Among clinical forms of the diseases moderately severe was the prevalent one (83-66.4 %). Lethal cases were not registered.